Development E-LKPD Based on High Order Thinking Skills (HOTS) - Rahayu, Sri; Ladamay, Iskandar; Wiyono, Bambang Budi; Susanti, Romia Hari; Purwito, Naufal Rafif (International Journal of Elementary Education, 2021)
Student Worksheet (LKPD) so far only contains black and white writing, doesn’t contain much picture and the questions presented don’t interest students to learn. The purpose of this research is to develop Electronic LKPD (E-LKPD) thematic learning based on High Order Thinking Skill (HOTS). Type of research is (Research & Development). The development model uses ADDIE. E-LKPD product that successfull developed then try it out to validators to determine the effectiveness. Data analysis carried out by qualitative and quantitative. Validation carried out by three validators, namely content, material and language validators. Research instrument use teacher and student response questionnaire for practicality and attractiveness. Result of validation media experts is 3.6 with "very valid" category, material expert is 3.83 with "very valid" category and linguist is 2.83 with "valid" category with revisions. The results of analysis the practicality E-LKPD can be assessed from teacher's questionnaire score obtained 3.43 with "very practical" category while results of analysis the attractiveness E-LKPD obtained from results of student questionnaire score 3.19 with "good" category. Based on the trial, it was concluded that the results of developing products of E-LKPD thematic learning based on HOTS were valid, practical and interesting to use in class IV learning.